A method for purifying non-weakly magnetic tailings to produce concentrate and the concentrate obtained

Through the combination process of acid leaching method and flotation method, the problem of low purity and recovery of quartz, mica and fluorite concentrate in secondary tungsten tailings was solved, and the production of concentrate with high purity and high recovery was achieved. The problem of difficulty in taking into account both purity and recovery rate in the prior art is promoted, and resource recycling and environmental protection are promoted.

CN114130541BActive Publication Date: 2024-12-31SHENZHEN KOALA ECOLOGICAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111381147.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-09-30
Filing Date
2021-11-20
Publication Date
2024-12-31
Estimated Expiration
2041-11-20

AI Technical Summary

Technical Problem

The prior art is difficult to effectively separate and purify quartz, mica and fluorite through physical ore dressing methods in secondary tungsten tailings, resulting in low purity of concentrate and low recovery rate, and there is a dilemma between improving purity and recovery rate. Can't take into account both.

Method used

Using the combination process of acid leaching method and flotation method, firstly separate calcite and dolomite by reaction of hydrochloric acid and non-weak magnetic tailings, then extract fluorite, mica and quartz concentrate respectively by flotation method, and control the acid leaching solution and float. The pH value of the ore dressing slurry and the combination of additives can achieve selective separation of minerals.

Benefits of technology

It significantly improves the purity and recovery rate of fluorite, mica and quartz concentrate, breaks through the dilemma between concentrate purity and recovery rate, and realizes resource recycling and environmentally friendly production processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003365601050000061
    Figure BDA0003365601050000061
  • Figure BDA0003365601050000071
    Figure BDA0003365601050000071
  • Figure BDA0003365601050000091
    Figure BDA0003365601050000091
Patent Text Reader

Abstract

The present application relates to the technical field of tailings purification, and specifically discloses a method for purifying non-weakly magnetic tailings to produce concentrate and the prepared concentrate. The method is: S1, acid leaching I; S2, flotation I; S3, flotation II; S4, acid leaching II. A concentrate is purified by the above method, and the prepared concentrate includes fluorite concentrate, mica concentrate and quartz concentrate. The preparation method of the present application can be used to prepare fluorite concentrate, mica concentrate and quartz concentrate with high purity and high recovery rate.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The priority basis of the present invention includes: an invention application with an application date of September 30, 2021, application number 2021111612834, and patent name "A method and equipment for preparing quartz purified from secondary tungsten tailings". Technical Field

[0002] The present application relates to the technical field of tailings purification, and more specifically, to a method for purifying non-weakly magnetic tailings to produce concentrate and the prepared concentrate. Background Art

[0003] Non-weakly magnetic tailings are obtained by removing weakly magnetic minerals from secondary tungsten tailings during the strong magnetic separation process. Non-weakly magnetic tailings contain (calcite, dolomite) minerals, and there are still a small number of fine particles in the (calcite, dolomite) minerals that have not been dissociated from the (fluorite, mica, quartz) minerals, and they are still intergrown. The particle size of non-weakly magnetic tailings is fine, and most of the minerals in the tailings (dolomite, calcite, mica, fluorite, quartz) are intergrown without monomer dissociation. If the (muscomica, quartz, fluorite) concentrate obtained by flotation using physical beneficiation methods is not high in purity and has a low recovery rate. Summary of the invention

[0004] In order to simultaneously improve the purity and recovery rate of the concentrate, the present application provides a method for purifying non-weakly magnetic tailings to produce concentrate and the prepared concentrate.

[0005] In the first aspect, the present application provides a method for purifying non-weakly magnetic tailings to produce concentrate, which adopts the following technical solution:

[0006] S1. Acid leaching I: Mix the hydrochloric acid solution with the non-weakly magnetic tailings under stirring until the pH of the leaching solution is 1-3, and then stir for 8-15 minutes, and then perform solid-liquid separation I to obtain filter residue I and filtrate I, and rinse the filter residue I with clean water until the pH value of the leaching water is 4-6;

[0007] S2, flotation I: the washed filter residue I is mixed with water to obtain a flotation pulp I with a mass ratio of 30-40%, quartz and mica inhibitors and fluorite collector are added to the flotation pulp I in sequence, and flotation operation is performed. After flotation 5-7 times, fluorite concentrate and quartz and mica mixed minerals are obtained;

[0008] S3, flotation II: quartz and mica mixed minerals are mixed with water to form flotation pulp II with a mass ratio of 30-40%, pH regulator is added to flotation pulp II to adjust the pH to 3-4, then quartz depressant and mica collector are added in sequence to carry out flotation operation, and mica concentrate and quartz rough concentrate are obtained after 2-3 flotation operations;

[0009] S4, acid leaching II: Mix the quartz crude concentrate with the boric acid leaching solution, then heat to 45-50°C, and stir at 45-50°C for 10-30 minutes, then perform solid-liquid separation II to obtain filter residue II and filtrate II, rinse the filter residue II with clean water until the pH value of the leaching water is 6-7, at this time, the filter residue II is a high-purity quartz concentrate.

[0010] The process of purifying and producing concentrate in this application:

[0011] Non-weakly magnetic minerals (including fluorite, quartz, calcite, dolomite, mica, and other minerals (mainly feldspar)) are mixed with hydrochloric acid solution. At this time, hydrochloric acid reacts chemically with the monomer-dissociated calcite (CaCO3) and dolomite in the non-weakly magnetic minerals, as well as the calcite (CaCO3) and dolomite (MgCO3) in the [(dolomite, calcite) and (mica, fluorite, quartz)] intergrowth to generate water-soluble calcium chloride and magnesium chloride, which enter the acid leaching solution I. Fluorite is slightly soluble in hydrochloric acid, while quartz and mica are insoluble in hydrochloric acid and exist in the acid leaching solution I in solid form. After solid-liquid separation, filter residue I (filter residue I contains mixed minerals of fluorite, quartz, and mica) and filtrate I (filtrate I is acid leaching solution I, which contains calcium and chloride ions);

[0012] The filter residue I (filter residue I contains mixed minerals of fluorite, quartz and mica) enters flotation I, and fluorite collector and quartz and mica inhibitors are added to the flotation pulp I to carry out flotation operation. After the flotation operation, fluorite concentrate and mixed minerals of quartz and mica are obtained;

[0013] The mixed minerals of quartz and mica enter the flotation II production process, and a pH regulator is added to the flotation pulp II to adjust the pH to 3-4, and then a mica collector and a quartz depressant are added to carry out flotation operations. After the flotation operation, mica concentrate and quartz rough concentrate are obtained (the quartz rough concentrate contains a small amount of fluorite, and a very small amount of mica and other minerals);

[0014] Mixing quartz rough concentrate (quartz rough concentrate contains a small amount of fluorite, and a very small amount of mica and other minerals) with boric acid leaching solution, the boric acid leaching solution reacts with the fluorite in the quartz rough concentrate to generate calcium chloride and hydrofluoric acid, and the hydrofluoric acid reacts with boric acid to generate fluoroboric acid, thereby preventing the reaction of hydrofluoric acid with quartz, so that quartz exists in the acid leaching solution II in a solid form; flotation operation is carried out, and after the flotation operation, filter residue II (filter residue II is high-purity quartz concentrate) and filtrate II (filtrate II is acid leaching solution II, which contains calcium, chloride ions, fluoroboric acid and boric acid) are obtained.

[0015] Containing (calcite, dolomite) minerals in non-weak magnetic tailings, there is still a small part of fine-grained grade in (calcite, dolomite) minerals and no monomer dissociation between (fluorite, mica, quartz) minerals, and they are still intergrown. At this time, if physical beneficiation method is adopted for flotation, the purity of the obtained (mucomica, quartz, fluorite) concentrate is not high, and the requirement of demand industry is not met and the recovery rate is low. To overcome the above-mentioned defects, in the present application, acid leaching method is first adopted, and (calcite, dolomite) minerals are selectively first dissolved with hydrochloric acid, and (fluorite, mica, quartz) minerals are not dissolved by hydrochloric acid, and the purpose of separating (fluorite, mica, quartz) minerals from (calcite, dolomite) minerals is reached, and then physical beneficiation method is adopted for flotation, and the fluorite concentrate, mica concentrate and quartz concentrate obtained respectively are obtained.

[0016] This application adopts the production process of acid leaching → flotation → acid leaching, and the obtained fluorite concentrate, mica concentrate and quartz concentrate are of high purity, meet the requirements of the industry, and have a high recovery rate. Compared with the physical flotation method currently used in China, this application has much higher purity and recovery rate of the concentrate, breaking through the dilemma that in the mineral processing production process, only one of the purity and recovery rate of the concentrate can be chosen, and both cannot be taken into account (the purity of the concentrate is inversely proportional to the recovery rate, that is, the higher the purity of the concentrate, the lower the recovery rate).

[0017] In the present application, filtrate I and rinsing water I can enter the precipitation production process for precipitation operation; filtrate II and rinsing water II can enter the recovery production process, and can be used to produce high-purity ammonia water, hydrochloric acid and boric acid, as well as calcium sulfate and magnesium sulfate chemical products, which is pollution-free to the environment, realizes the recycling of resources, and saves costs.

[0018] Preferably, the concentration of the hydrochloric acid solution is 0.8-1.4 mol / L, and most preferably, the concentration of the hydrochloric acid solution is 1 mol / L.

[0019] When the concentration of hydrochloric acid is 0.8-1.4 mol / L, fluorite is slightly soluble in hydrochloric acid, when the concentration of hydrochloric acid is greater than 1.5 mol / L, fluorite will dissolve slowly, and when the concentration of hydrochloric acid is greater than 3 mol / L, fluorite will dissolve quickly. Therefore, in this application, the concentration of the hydrochloric acid solution is controlled at 0.8-1.4 mol / L, which can reduce the dissolution of fluorite and help improve the recovery rate of fluorite concentrate.

[0020] Preferably, in the step of acid leaching I, when the hydrochloric acid solution is mixed with the non-weakly magnetic tailings, the hydrochloric acid solution is first added at a flow rate of 40-50 L / min, and then added at a flow rate of 8-12 L / min after no large number of bubbles are generated in the solution; further preferably, optimally, the hydrochloric acid solution is first added at a flow rate of 50 L / min, and then added at a flow rate of 10 L / min after no large number of bubbles are generated in the solution.

[0021] By adopting the above technical solution, the hydrochloric acid solution is initially added at a flow rate of 40-50 L / min, which can quickly dissolve most of the calcite and dolomite, thereby improving efficiency. Subsequently, the hydrochloric acid is added at a flow rate of 8-12 L / min, which can reduce the dissolution of fluorite by the hydrochloric acid, thereby improving the recovery rate of fluorite. When there are no large amounts of bubbles in the solution, it means that most of the calcite and dolomite have been dissolved. At this time, it is necessary to reduce the flow rate of the hydrochloric acid, that is, to reduce the concentration of the hydrochloric acid, thereby preventing the fluorite from being dissolved by the high concentration of hydrochloric acid.

[0022] When conventionally adding hydrochloric acid, it is necessary to first detect the content of calcite and dolomite in non-weak magnetic separation minerals, and then calculate the volume of hydrochloric acid required to be added, and the corresponding hydrochloric acid of different concentrations must be selected according to the different calcite contents in non-weak magnetic separation minerals, and the calculation is complicated and cumbersome. However, when adding hydrochloric acid using the method of the present application, there is no problem of complex and cumbersome calculations, and the corresponding hydrochloric acid of different concentrations must be selected according to the different calcite contents in non-weak magnetic separation minerals. It is simple, convenient, and easy to implement.

[0023] Preferably, the fluorite collector is triethanolamine oleate, and the usage of the triethanolamine oleate is 100-300 g / t.

[0024] Triethanolamine oleate has excellent emulsification and dispersibility in water, strong foaming ability, fine foam, strong stability in acidic and alkaline media, and good flotation effect on fine-grained fluorite. In addition, when triethanolamine oleate is used for flotation of fluorite, it does not need to add emulsifiers, surfactants or foaming agents, which can reduce costs and does not pollute the environment.

[0025] Preferably, the quartz and mica inhibitors are water glass and acidified water glass.

[0026] Further preferably, the number of flotation in step S2 flotation I is 6 times (I-VI), specifically as follows:

[0027] Ⅰ: Mix the washed filter residue Ⅰ with water to obtain flotation pulp Ⅰ with a mass ratio of 30-40%, add sodium carbonate to the flotation pulp Ⅰ to adjust the pH to 7.5-8.5, then add 1500-2000g / t of water glass and 100-300g / t of triethanolamine oleate in sequence, stir, and perform flotation operation. After the flotation operation, quartz and mica mixed minerals and foam Ⅰ are obtained;

[0028] Ⅱ: Add 300-500g / t of water glass and 50-100g / t of triethanolamine oleate to the foam Ⅰ in sequence, stir, and perform flotation operation. After the flotation operation, a mixed mineral of quartz and mica and foam Ⅱ are obtained;

[0029] III: Add 700-1000 g / t of acidified water glass and 50-100 g / t of triethanolamine oleate to the foam II in sequence, stir, and perform flotation operation. After the flotation operation, a mixed mineral of quartz and mica and foam III are obtained;

[0030] IV: Add 500-800 g / t of acidified water glass and 20-50 g / t of triethanolamine oleate to the foam III in sequence, stir, and perform flotation operation. After the flotation operation, a mixed mineral of quartz and mica and foam IV are obtained;

[0031] V: adding 500-800 g / t of acidified water glass and 10-30 g / t of triethanolamine oleate to the foam IV in sequence, stirring, and performing flotation operation. After the flotation operation, a mixed mineral of quartz and mica and foam V are obtained;

[0032] VI: Add 100-300 g / t of acidified water glass to the foam V, stir, and perform flotation operation. After the flotation operation, a mixed mineral of quartz and mica and foam VI are obtained; the foam VI is fluorite concentrate.

[0033] By adopting the above technical scheme, during the rough flotation of fluorite (I-II flotation), water glass inhibitor is added to make fluorite enter into the rough fluorite concentrate as much as possible, thereby improving the recovery rate of fluorite; and during the fine flotation of the rough fluorite concentrate (III-VI flotation), the role of acidified water glass is to increase the CaF2 content in the fluorite concentrate and improve the purity of fluorite. Therefore, in the flotation process of fluorite, water glass is added during rough flotation and acidified water glass is added during fine flotation, which can simultaneously improve the recovery rate and purity of fluorite.

[0034] Acidified water glass, water glass and sodium carbonate cooperate with each other to have a strong selective inhibitory effect on silicon dioxide, but when the amount of acidified water glass is too large, it will hinder the adsorption of triethanolamine oleate on the surface of fluorite, and produce a strong inhibitory effect on fluorite. Therefore, according to the above ratio, the present application can achieve the purpose of selectively inhibiting silicon dioxide. According to the above method for flotation of fluorite, it has an inhibitory effect on calcite (CaCO3) and dolomite (CaCO3, MgCO3), can exclude the adsorption and collection of calcium ions and magnesium ions on the surface of calcite and dolomite, and achieve the final inhibition of calcite and dolomite. At the same time, this effect has a high selectivity, so that the flotation of fluorite is not significantly affected.

[0035] According to the method of the present application, the fluorite (CaF2) content in the prepared fluorite concentrate is ≥97%, which meets the requirements of the required industry, and the fluorite recovery rate is greater than 88%.

[0036] Preferably, the pH regulator is sulfuric acid, the dosage of the mica collector is 50-100 g / t, the mica collector is any one of dodecylamine, octadecylamine, mixed amine and dodecyl coconut amine, and more preferably, the mica collector is dodecylamine.

[0037] The flotation of mica is divided into acidic and alkaline flotation. Under acidic conditions, cationic collectors are effective agents, while under alkaline conditions, anionic and cationic mixed collectors need to be used in combination. When flotation is carried out under alkaline conditions, when anionic and cationic mixed collectors are used, there are strict requirements on the ratio of anionic and cationic mixed collectors, and in the production process, the ratio of anionic and cationic mixed collectors is not easy to control, which will increase the difficulty of flotation and the quality of concentrate products. The quality of concentrate products is unstable and fluctuates greatly. In acidic conditions, the use of any one of dodecylamine, octadecylamine, mixed amines and dodecyl coconut amine as a collector for the flotation of mica has the advantages of convenient procurement, wide sources, low price, and easy solubility.

[0038] In addition, in the present application, the content of mica in the mixed ore (quartz, mica) left at the bottom of the flotation tank after the flotation of fluorite is low and the mineral composition in the mixed ore is simple, basically only quartz and mica. Therefore, under acidic conditions, and when the mica collector uses a dodecylamine cationic collector to collect mica, the mica concentrate after flotation has a high yield, high recovery and good purity.

[0039] Preferably, the dosage of the quartz inhibitor is 4-6 kg / t, and the quartz inhibitor is any one of sodium hexametaphosphate, water glass, carboxymethyl cellulose, oxalic acid and citric acid. Most preferably, the quartz inhibitor is sodium hexametaphosphate.

[0040] The mica to be floated exists in the mixed ore (quartz, mica) left at the bottom of the flotation tank after the flotation of fluorite. When floating mica, any one of sodium hexametaphosphate, water glass, carboxymethyl cellulose, oxalic acid and citric acid can be selected as a quartz inhibitor. Under the same flotation conditions, sodium hexametaphosphate, carboxymethyl cellulose, water glass and citric acid were tested for inhibiting quartz flotation, and it was found that sodium hexametaphosphate had the best effect in inhibiting quartz. Therefore, in this application, sodium hexametaphosphate is preferably used as an inhibitor for inhibiting quartz.

[0041] When 50-100g / t of dodecylamine (mica collector) is used for floating mica, 4-6Kg / t of sodium hexametaphosphate (quartz flotation depressant) is added to achieve the best flotation effect, and a mica concentrate with high purity, high recovery rate and high yield is obtained. The recovery rate of the obtained mica concentrate is greater than 89%, and the mica content in the mica concentrate is ≥94%, which meets the requirements of the required industry. Preferably, the boric acid leaching solution includes a hydrochloric acid solution with a concentration of 3-6mol / L and boric acid, and the mass concentration of boric acid in the boric acid leaching solution is 10-15%. Most preferably, the boric acid leaching solution includes a hydrochloric acid solution with a concentration of 4mol / L and boric acid, and the mass concentration of boric acid in the boric acid leaching solution is 10%.

[0042] Further preferably, the boric acid leaching solution is prepared by the following preparation process:

[0043] The hydrochloric acid is heated to 45-60°C, and then solid boric acid is added to obtain a boric acid leaching solution with a boric acid concentration of 10-15%. Most preferably, the hydrochloric acid with a concentration of 4 mol / L is heated to 50°C, and then solid boric acid is added to obtain a boric acid leaching solution with a boric acid concentration of 10%.

[0044] When preparing the boric acid leaching solution, the hydrochloric acid is first heated to 45-50°C, and then the boric acid solid is added, so as to increase the solubility of the boric acid to 10%, thereby preventing the reaction of quartz with hydrofluoric acid and improving the purity and recovery rate of the quartz concentrate.

[0045] According to the method of the present application, the recovery rate of the obtained quartz concentrate is greater than 97%, and the content of SiO2 in the quartz concentrate is ≥99.50%, which meets the requirements of the required industry.

[0046] In the second aspect, the present application provides a concentrate, which adopts the following technical solution:

[0047] A concentrate is obtained by purification by the above method, and the concentrate includes fluorite concentrate, mica concentrate and quartz concentrate.

[0048] This application adopts the production process of acid leaching → flotation → acid leaching to obtain high-purity mica concentrate, quartz concentrate and fluorite concentrate. The fluorite (CaF2) content in the fluorite concentrate is ≥97%, the mica content in the mica concentrate is ≥94%, and the SiO2 content in the quartz concentrate is ≥99.50%, which meets the requirements of the demand industry. The recovery rates of mica concentrate, quartz concentrate and fluorite concentrate are also very high, with a fluorite recovery rate of more than 88%, a mica recovery rate of more than 89%, and a quartz recovery rate of more than 97%.

[0049] In summary, this application has the following beneficial effects:

[0050] The present application adopts the production process of acid leaching → flotation → acid leaching, and the obtained (mica, quartz, fluorite) concentrates are of high purity, meeting the requirements of the demanding industry, and the recovery rates of various concentrates are also high; in addition, compared with the physical flotation method currently used in China, in the present application, both the purity and the recovery rate of the concentrate are much higher, breaking through the dilemma that the purity and recovery rate of the concentrate cannot be achieved at the same time in the mineral processing production process. DETAILED DESCRIPTION

[0051] The present application is further described in detail with reference to the following examples. It should be noted that if no specific conditions are specified in the following examples, the conventional conditions or the conditions recommended by the manufacturer shall be followed; the raw materials used in the following examples can be obtained from common commercial sources unless otherwise specified.

[0052] Acidified water glass: sulfuric acid 5%: water glass 5% = 1:1 (volume ratio);

[0053] Sulfuric acid 5%: commercial concentrated sulfuric acid: water = 1:19 (volume ratio);

[0054] Water glass 5%: Commercially available concentrated water glass: water = 1:19 (volume ratio).

[0055] Preparation Example

[0056] The preparation of boric acid leaching solution is as follows:

[0057] A 4 mol / L hydrochloric acid solution is heated to 50° C., and then solid boric acid is added under stirring, with hydrochloric acid: solid boric acid = 100:10 (volume-to-mass ratio). After complete dissolution, a boric acid leaching solution is obtained, in which the mass concentration of boric acid is 10%.

[0058] In the actual flotation process, the required amount of boric acid leaching solution can be prepared according to the preparation method of boric acid leaching solution.

[0059] Example

[0060] The non-weakly magnetic minerals (including fluorite, quartz, calcite, dolomite, mica, and other minerals (mainly feldspar)) were crushed and ground to a particle size of -0.074 mm, and then mixed and sampled for multi-element analysis and mineral phase analysis. The results of multi-element analysis and mineral phase analysis of non-weakly magnetic minerals are shown in Table 1.

[0061] Table 1 Multi-element and mineral phase information of non-weakly magnetic minerals

[0062]

[0063]

[0064] Example 1

[0065] 100 kg of non-weakly magnetic minerals crushed and ground to a particle size of -0.074 mm are mixed with 1 mol / L hydrochloric acid solution, the mass volume ratio of the non-weakly magnetic minerals to the hydrochloric acid is 1:1.5 (at this time, the pH of the leaching solution is about 1), and stirred for 10 minutes; at this time, the hydrochloric acid reacts chemically with calcite (CaCO3) and dolomite (MgCO3) to generate calcium chloride and magnesium chloride that are easily soluble in water and enter the acid leaching solution I, fluorite is slightly soluble in hydrochloric acid, while quartz and mica are insoluble in hydrochloric acid and exist in the acid leaching solution I in solid form. After solid-liquid separation, filter residue I (filter residue I contains mixed minerals of fluorite, quartz, and mica) and filtrate I (filtrate I is acid leaching solution I, which contains calcium and chloride ions) are obtained, and the filter residue I is rinsed with clean water until the pH value of the leaching water is 5;

[0066] Ⅰ: The leached filter residue Ⅰ (containing fluorite, quartz, mica mixed minerals) is mixed with water at a mass ratio of 30:100 to obtain flotation pulp Ⅰ, sodium carbonate is added to the flotation pulp Ⅰ to adjust the pH to 8, and then 1500g / t of water glass and 300g / t of triethanolamine oleate are added in sequence, stirred, and flotation operation is performed. After the flotation operation, quartz and mica mixed minerals and foam Ⅰ are obtained;

[0067] Ⅱ: 500 g / t of water glass and 100 g / t of triethanolamine oleate are added to the foam Ⅰ in sequence, stirred, and flotation is performed. After the flotation, a mixed mineral of quartz and mica and foam Ⅱ are obtained;

[0068] III: Add 1000 g / t of acidified water glass and 80 g / t of triethanolamine oleate to the foam II in sequence, stir, and perform flotation operation. After the flotation operation, a mixed mineral of quartz and mica and foam III are obtained;

[0069] IV: 600 g / t of acidified water glass and 30 g / t of triethanolamine oleate are added to the foam III in sequence, stirred, and flotation is performed. After the flotation, a mixed mineral of quartz and mica and foam IV are obtained;

[0070] V: 500 g / t of acidified water glass and 20 g / t of triethanolamine oleate are added to the foam IV in sequence, stirred, and flotation is performed. After the flotation, a mixed mineral of quartz and mica and foam V are obtained;

[0071] VI: Add 300 g / t of acidified water glass to the foam V, stir, and perform flotation operation. After the flotation operation, a mixed mineral of quartz and mica and foam VI are obtained; the foam VI is fluorite concentrate;

[0072] Mixing quartz and mica mixed minerals with water at a mass ratio of 30:100 to obtain flotation pulp II, adjusting the pH of flotation pulp II to 3 with sulfuric acid, then adding 4kg / t sodium hexametaphosphate (quartz inhibitor) and 50g / t dodecylamine (mica collector) to flotation pulp II to carry out flotation operation, and obtaining mica concentrate and quartz rough concentrate (quartz rough concentrate contains a small amount of fluorite, and a very small amount of mica and other minerals) after flotation operation;

[0073] Mix a pumice quartz concentrate (the quartz concentrate contains a small amount of fluorite, and a very small amount of mica and other minerals) with a boric acid leaching solution (prepared in the preparation example), the mass ratio of the quartz concentrate to the boric acid leaching solution is 1:1, the boric acid leaching solution reacts with the fluorite in the quartz concentrate to generate calcium chloride and hydrofluoric acid, and the hydrofluoric acid reacts with the boric acid to generate fluoroboric acid, thereby preventing the hydrofluoric acid from reacting with the quartz, and the quartz exists in the acid leaching solution II in a solid form; flotation operation is performed, and after the flotation operation, filter residue II (quartz concentrate) and filtrate II (acid leaching solution II, which contains calcium, chloride ions, fluoroboric acid and boric acid) are obtained; the filtrate I and the leaching water I are put into a precipitation production operation for precipitation operation; the filtrate II and the leaching water II can enter a recovery production process and can be used to produce high-purity ammonia water, hydrochloric acid, boric acid, and calcium sulfate and magnesium sulfate chemical products.

[0074] Embodiment 2-4

[0075] The difference between Example 2-4 and Example 1 is that the concentration of the hydrochloric acid solution is different in Example 2-4, and the rest is the same as Example 1. The details are shown in Table 2 below.

[0076] Table 2

[0077] Example Hydrochloric acid concentration mol / L Example 2 0.8 Example 3 1.5 Example 4 3.0

[0078] Example 5

[0079] The only difference between Example 5 and Example 1 is that in Example 5, when the hydrochloric acid solution is mixed with the non-weakly magnetic tailings, the hydrochloric acid solution is first added at a flow rate of 50 L / min, and then added at a flow rate of 10 L / min after no large amount of bubbles are generated in the solution, and the rest is the same as Example 1. The details are as follows:

[0080] 100 kg of non-weakly magnetic minerals crushed and ground to a particle size of -0.074 mm were mixed with 1 mol / L hydrochloric acid solution. The hydrochloric acid solution was first added at a flow rate of 50 L / min. At this time, hydrochloric acid reacted with calcite (CaCO3) and dolomite (MgCO3) to generate calcium chloride and magnesium chloride that were easily soluble in water and entered the acid leaching solution I until no large amount of bubbles were generated in the solution (indicating that most of the calcite (CaCO3) and dolomite (MgCO3) had dissolved). Subsequently, the hydrochloric acid solution was added at a flow rate of 10 L / min. When the pH value of the leaching solution was 1, the addition of hydrochloric acid was stopped. The mixture was stirred for 10 minutes. After solid-liquid separation, filter residue I (filter residue I contained mixed minerals of fluorite, quartz and mica) and filtrate I (filtrate I was acid leaching solution I, which contained calcium and chloride ions) were obtained. The filter residue I was rinsed with clean water until the pH value of the leaching water was 5.

[0081] Ⅰ: The leached filter residue Ⅰ (containing fluorite, quartz, mica mixed minerals) is mixed with water at a mass ratio of 30:100 to obtain flotation pulp Ⅰ, sodium carbonate is added to the flotation pulp Ⅰ to adjust the pH to 8, and then 1500g / t of water glass and 300g / t of triethanolamine oleate are added in sequence, stirred, and flotation operation is performed. After the flotation operation, quartz and mica mixed minerals and foam Ⅰ are obtained;

[0082] Ⅱ: 500 g / t of water glass and 100 g / t of triethanolamine oleate are added to the foam Ⅰ in sequence, stirred, and flotation is performed. After the flotation, a mixed mineral of quartz and mica and foam Ⅱ are obtained;

[0083] III: Add 1000 g / t of acidified water glass and 80 g / t of triethanolamine oleate to the foam II in sequence, stir, and perform flotation operation. After the flotation operation, a mixed mineral of quartz and mica and foam III are obtained;

[0084] IV: 600 g / t of acidified water glass and 30 g / t of triethanolamine oleate are added to the foam III in sequence, stirred, and flotation is performed. After the flotation, a mixed mineral of quartz and mica and foam IV are obtained;

[0085] V: 500 g / t of acidified water glass and 20 g / t of triethanolamine oleate are added to the foam IV in sequence, stirred, and flotation is performed. After the flotation, a mixed mineral of quartz and mica and foam V are obtained;

[0086] VI: Add 300 g / t of acidified water glass to the foam V, stir, and perform flotation operation. After the flotation operation, a mixed mineral of quartz and mica and foam VI are obtained; the foam VI is fluorite concentrate;

[0087] Mixing quartz and mica mixed minerals with water at a mass ratio of 30:100 to obtain flotation pulp II, adjusting the pH of flotation pulp II to 3 with sulfuric acid, then adding 4 kg / t sodium hexametaphosphate (quartz inhibitor) and 50 g / t dodecylamine (mica collector) to flotation pulp II to perform flotation operation, and obtaining mica concentrate and quartz rough concentrate (quartz rough concentrate contains a small amount of fluorite, and a very small amount of mica and other minerals) after flotation operation;

[0088] Mix a pumice quartz concentrate (the quartz concentrate contains a small amount of fluorite, and a very small amount of mica and other minerals) with a boric acid leaching solution (prepared in the preparation example), the mass ratio of the quartz concentrate to the boric acid leaching solution is 1:1, the boric acid leaching solution reacts with the fluorite in the quartz concentrate to generate calcium chloride and hydrofluoric acid, and the hydrofluoric acid reacts with the boric acid to generate fluoroboric acid, thereby preventing the hydrofluoric acid from reacting with the quartz, and the quartz exists in the acid leaching solution II in a solid form; flotation operation is performed, and after the flotation operation, filter residue II (quartz concentrate) and filtrate II (acid leaching solution II, which contains calcium, chloride ions, fluoroboric acid and boric acid) are obtained.

[0089] Filtrate I and rinsing water I enter the precipitation production process for precipitation operation; filtrate II and rinsing water II can enter the recovery production process and can be used to produce high-purity ammonia water, hydrochloric acid, boric acid, and calcium sulfate and magnesium sulfate chemical products.

[0090] Example 6

[0091] The only difference between Example 6 and Example 5 is that in Example 6, the fluorite collector is sodium oleate, and the rest is consistent with Example 5.

[0092] Embodiment 7-11

[0093] The difference between Example 7-11 and Example 5 is that in Example 7-11, the amount of fluorite collector used is different, and the rest is the same as Example 5, as shown in Table 3 below.

[0094] Table 3

[0095]

[0096]

[0097] Examples 12-19

[0098] The difference between Examples 12-19 and Example 5 is that in Examples 12-19, the selection and dosage of the mica collector and the quartz inhibitor are different, and the rest are the same as Example 5, as shown in Table 4 below.

[0099] Table 4

[0100]

[0101] Comparative Example

[0102] Comparative Example 1

[0103] The only difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, there is no step S1, acid leaching I, that is, the non-weakly magnetic mineral with a particle size of -0.074 mm after crushing and grinding is directly mixed with water to prepare flotation pulp I, and the rest is consistent with Example 1.

[0104] Performance testing

[0105] The yield, purity and recovery rate of the fluorite concentrate, mica concentrate and quartz concentrate prepared in Examples 1-19 and Comparative Example 1 were detected, and the specific data are shown in Table 5 below.

[0106] Table 5

[0107]

[0108]

[0109] 1. Yield

[0110] The calculation of mineral yield and recovery rate is divided into theoretical and practical types. The yield described in this invention refers to the actual yield, that is, the mass of a certain product (such as quartz concentrate) divided by the mass percentage of non-weakly magnetic minerals. Therefore, the calculation of yield is the individual mass of individual products divided by the input mass of non-weakly magnetic minerals.

[0111] For example, in Example 5, the mass of quartz concentrate obtained after 100 kg of non-weakly magnetic minerals are purified through the production process is 68.55 kg, that is,

[0112]

[0113] 2. Recovery rate

[0114] The recovery rate described in the present invention refers to the actual recovery rate, that is, the mass of a certain product (such as quartz concentrate) obtained is multiplied by the silicon dioxide content as the numerator, the mass of non-weakly magnetic minerals is multiplied by the content of pure quartz (100% silicon dioxide) in the non-weakly magnetic minerals (70.0%) as the denominator, and the recovery rate is obtained by dividing them and then multiplying by 100%.

[0115] The actual recovery rate is calculated as follows:

[0116] Actual recovery rate = [(actual mass of a certain (quartz / mica / fluorite) concentrate (kg) × (percentage content of a certain element and compound in a certain (quartz / mica / fluorite) concentrate (%)] ÷ [(processing amount (input amount) of non-weakly magnetic minerals (kg) × (percentage content of a certain element and compound in a certain pure substance (quartz / mica / fluorite) in non-weakly magnetic minerals (%))] × 100%.

[0117] For example, in Example 5, the mass of quartz concentrate obtained after 100kg of non-weakly magnetic minerals is purified by the production process is 68.55kg, of which silicon dioxide is 99.51%, and the mass of pure quartz (silicon dioxide is 100%) in the non-weakly magnetic minerals is 70.0kg. That is,

[0118] Actual recovery rate of quartz = (68.55 × 99.51%) ÷ (100 × 70.0%) × 100% = 97.44%

[0119] 3. Content

[0120] The content is also called percentage content, which refers to the ratio of the mass of a certain element or compound (such as silicon dioxide in quartz concentrate products) in a certain mineral (such as non-weakly magnetic minerals) or a certain product (such as quartz concentrate) to the total mass of a certain mineral (such as non-weakly magnetic minerals) or a certain product (such as quartz concentrate). For example, the content of silicon dioxide in quartz concentrate products is 99.50%, which means that in the quartz product, silicon dioxide accounts for 99.50%, and there is 0.5% of other substances.

[0121] The mica concentrate product described in the present invention includes mica and a small amount of quartz, and the silicon dioxide content in the mica concentrate product is the total content of silicon dioxide and quartz in the mica. The content (also called purity) of pure mica (mica content is 100%) in the mica concentrate product is obtained by multiplying the content of AI2O3 in the mica concentrate product by the conversion coefficient (2.5974) and then dividing it by the mass of the mica concentrate product. The content of AI2O3 in the mica concentrate product can be considered as that in pure mica. Because the proportion of other minerals in non-weakly magnetic minerals is less than 0.5%, and a part of them will enter the acid leaching solution and the fluorite concentrate in the acid leaching production process and the fluorite flotation production process. So it can be ignored and not included.

[0122] For example, in Example 5, the mass of mica concentrate obtained after the purification production process of 100 kg of non-weakly magnetic minerals is 68.55 kg, the content of AI2O3 in the mica concentrate is 36.53%, and the molecular formula of mica is KAI2[AISi3O10}[OH]2, of which silicon dioxide accounts for 45.2% and aluminum oxide accounts for 38.5%.

[0123] The conversion factor between mica and AI2O3 is: That is, the pure mica content (purity) in the mica concentrate = 36.53% × 2.5974 = 94.88%.

[0124] Determination of the ratio of pure quartz (100% silicon dioxide) to pure mica in non-weakly magnetic minerals:

[0125] Since the proportion of other minerals in non-weakly magnetic minerals is less than 0.5%, the amount of pure quartz and pure mica contained is very small, so they can be ignored and not included. That is, the silica content in non-weakly magnetic minerals is the sum of the silica contents in pure quartz and pure mica, and the AI2O3 content in non-weakly magnetic minerals is the AI2O3 content in pure mica.

[0126] The molecular formula of mica is KAI2[AISi3O10][OH]2, of which silicon dioxide accounts for 45.2% and aluminum oxide accounts for 38.5%.

[0127] The conversion factor between mica and AI2O3 is: The conversion factor between mica and SiO2 is: We can get:

[0128] The proportion of pure mica in non-weakly magnetic minerals = 2.5974 × Al2O3 content in non-weakly magnetic minerals = 2.5974 × 3.08 = 8.0% The content of silicon dioxide in pure mica in non-weakly magnetic minerals = the proportion of pure mica in non-weakly magnetic minerals ÷ 2.2124 = 8.0% ÷ 2.2124 = 3.62%

[0129] The proportion of pure quartz in non-weakly magnetic minerals = the silicon dioxide content in non-weakly magnetic minerals - the silicon dioxide content in pure mica in non-weakly magnetic minerals = 73.62% - 3.62% = 70.0%

[0130] In combination with Example 2, it can be seen from Example 1 and Example 3 and Table 5 that in Example 2, when the concentration of hydrochloric acid is 0.8 mol / L, under the same other conditions, due to the high calcite content (14%) in the non-weak magnetic separation mineral, the calcite is not completely dissolved into the hydrochloric acid leaching solution, and part of the undissolved calcite in the hydrochloric acid leaching solution enters the filter residue after the acid leaching / filtration I production operation [a mixed ore of (quartz, fluorite, and mica)]. In the subsequent flotation production operation, due to the presence of calcite solids, a part of the calcite solids will also be floated into the fluorite concentrate and the mica concentrate when the fluorite and mica are separately floated, causing the fluorite concentrate (CaF2%) and the mica concentrate (mica%) content (purity) to decrease. Part of the calcite is intergrowth with fluorite and enters the filter residue [a mixed ore of (quartz, fluorite, and mica)] because it is not dissolved. When flotation of fluorite, part of it enters the fluorite concentrate, and the other part stays at the bottom of the flotation tank and enters the mixed ore of (quartz and mica). The recovery rate of fluorite concentrate also decreases. This shows that when the calcite content in the non-weak magnetic separation mineral is high (14%), the concentration of hydrochloric acid should be greater than 0.8 mol / L.

[0131] In combination with Example 4, it can be seen from Example 1 and Example 3 and Table 5 that in Example 4, when the concentration of hydrochloric acid is 3.0 mol / L, under the same other conditions, due to the high concentration of hydrochloric acid (3.0 mol / L), part of the fluorite in the non-weak magnetic separation mineral is dissolved into the hydrochloric acid leaching solution, which reduces the recovery rate of the fluorite concentrate. This indicates that when the calcite content in the non-weak magnetic separation mineral is certain, the concentration of hydrochloric acid cannot be greater than 1.5 mol / L.

[0132] Combining Examples 1 and 3 with Example 5 and Table 5, it can be seen that the purity (content) and recovery rate of the fluorite concentrate, mica concentrate and quartz concentrate obtained in the three embodiments are basically similar, but the hydrochloric acid leaching production operation in Examples 1-3 first stipulates a solid-liquid ratio of 1.0:1.5, and then adds the calculated volume of hydrochloric acid required to be added, and the corresponding hydrochloric acid of different concentrations should be selected according to the different calcite contents in the non-weak magnetic separation minerals, and the calculation is complicated and cumbersome. However, this problem does not exist in Example 5.

[0133] From the comparison of Examples 1-4 with Example 5 and the data in Table 5, it can be seen that after fixing a suitable concentration range of hydrochloric acid (0.8-1.4 mol / L), preferably 1.0 mol / L. Even if the calcite content in the non-weak magnetic separation mineral fluctuates greatly, it will not affect the reduction of the content and recovery rate of fluorite concentrate, mica concentrate, and quartz concentrate, and there is no problem of complex and cumbersome calculations, and it is necessary to select corresponding hydrochloric acid of different concentrations according to the different calcite contents in the non-weak magnetic separation minerals.

[0134] In conjunction with Example 6 and Comparative Example 5, it can be seen in conjunction with Table 5 that under the same conditions, when sodium oleate is used as a collector in Example 6, the fluorite concentrate (CaF2%) content (purity) and the recovery rate decrease, and the mica concentrate (mica%) content (purity) also decreases. This is because the effect of sodium oleate on capturing fluorite is lower than that of triethanolamine oleate, and because the effect of sodium oleate on capturing fluorite is low, all fluorite cannot be floated out and enter the fluorite concentrate. This part of fluorite that is not floated out stays at the bottom of the flotation tank and enters the mixed ore (mica, quartz). When floating mica, this part of fluorite also can be floated into the mica concentrate, causing the mica concentrate (mica%) content (purity) to decrease.

[0135] Combining Example 7 and Comparative Examples 8-10 and Table 5, it can be seen that under the same conditions, when the dosage of triethanolamine oleate in Example 7 is 50 g / L, the recovery rate of fluorite concentrate and the content (purity) of mica concentrate (mica%) decrease. This is because when the dosage of triethanolamine oleate is small, a part of fluorite is not floated out and enters the fluorite concentrate. This part of fluorite that is not floated out remains at the bottom of the flotation tank and enters the mixed ore (mica, quartz). When floating mica, this part of fluorite will also be floated into the mica concentrate, causing the content (purity) of the mica concentrate (mica%) to decrease.

[0136] Combining Example 11 and Comparative Examples 8-10 and Table 5, it can be seen that under the same conditions, when the amount of triethanolamine oleate in Example 11 is 400 g / L, the content (purity) of fluorite concentrate (CaF2%) decreases. This is because when the amount of triethanolamine oleate is high, a part of quartz and mica will also be captured and floated by triethanolamine oleate and enter the fluorite concentrate, which reduces the content (purity) of fluorite concentrate (CaF2%).

[0137] Combining Examples 6, 7, 11 and Comparative Examples 8-10 and Table 5, it can be seen that under the same conditions, when the dosage of triethanolamine oleate is in the range of 100-300 g / t, the flotation effect on fluorite is the best. The content (purity) and recovery rate of fluorite concentrate (CaF2%) are both high. When the dosage is equal, the effect of sodium oleate in capturing fluorite is lower than that of triethanolamine oleate.

[0138] Combining Examples 12-16 and Table 5, it can be seen that in Example 12, the recovery rate and purity of mica concentrate and quartz concentrate are higher, indicating that under the same conditions, when dodecylamine is selected as the mica collector and sodium hexametaphosphate is selected as the quartz inhibitor, it is beneficial to improve the recovery rate and purity of mica concentrate and quartz concentrate.

[0139] It can be seen from Examples 12, 17, and 18 and Table 5 that in Example 12, the recovery rate and purity of mica concentrate and quartz concentrate are higher, indicating that under the same conditions, according to the formula content of the present application, adding dodecylamine and sodium hexametaphosphate is beneficial to improving the recovery rate and purity of mica concentrate and quartz concentrate.

[0140] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for purifying non-weakly magnetic tailings to produce concentrate, characterized in that: The following steps are involved: S1. Acid leaching I: Mix the hydrochloric acid solution with the non-weakly magnetic tailings under stirring until the pH of the leaching solution is 1-3, and then stir for 8-15 minutes, and then perform solid-liquid separation I to obtain filter residue I and filtrate I, and rinse the filter residue I with clean water until the pH value of the leaching water is 4-6; S2, flotation I: the leached filter residue I is mixed with water to obtain a flotation pulp I with a mass ratio of 30-40%, quartz and mica inhibitors and fluorite collectors are sequentially added to the flotation pulp I to perform flotation operations, and fluorite concentrate and quartz and mica mixed minerals are obtained after 5-7 flotation operations; S3, flotation II: quartz and mica mixed minerals are mixed with water to form flotation pulp II with a mass ratio of 30-40%, pH regulator is added to flotation pulp II to adjust the pH to 3-4, then quartz depressant and mica collector are added in sequence to carry out flotation operation, and mica concentrate and quartz rough concentrate are obtained after 2-3 flotation operations; S4, acid leaching II: the quartz crude concentrate is mixed with the boric acid leaching solution, then heated to 45-50°C, and stirred at 45-50°C for 10-30 minutes, and then solid-liquid separation II is performed to obtain filter residue II and filtrate II, and the filter residue II is washed with clean water until the pH value of the washing water is 6-7. At this time, the filter residue II is a high-purity quartz concentrate; The concentration of the hydrochloric acid solution is 0.8-1.4 mol / L; In the acid leaching step I, when the hydrochloric acid solution is mixed with the non-weakly magnetic tailings, the hydrochloric acid solution is first added at a flow rate of 40-50 L / min, and then added at a flow rate of 8-12 L / min after no large amount of bubbles are generated in the solution; The pH regulator is sulfuric acid, the mica collector is any one of dodecylamine, octadecylamine, mixed amine and dodecyl coconut amine, and the dosage of the mica collector is 50-100 g / t; The dosage of the quartz inhibitor is 4-6 kg / t, and the quartz inhibitor is any one of sodium hexametaphosphate, water glass, carboxymethyl cellulose, oxalic acid and citric acid.

2. The method for purifying non-weakly magnetic tailings to produce concentrate according to claim 1, characterized in that: The fluorite collector is triethanolamine oleate, and the usage of the triethanolamine oleate is 100-300g / t.

3. The method for purifying non-weakly magnetic tailings to produce concentrate according to claim 2, characterized in that: The quartz and mica inhibitors are water glass and acidified water glass.